Reaching an Agreement for the Elimination of Child Labour from the Supply Chains - Haq, Md. Zahurul; Alam, A. S. A. Ferdous; Ayub, Zainal Amin; Farzana, Kazi Fahmida (ExcelingTech, 2020)
This article examines how child labour can be eliminated from various supply chains in Bangladesh. Reinforcing this issue is important to comply with international labour standards on child labour and to avoid potential trade sanctions of various types. Drawing upon the examples of other mechanisms to implement international labour standards particularly in a situation when domestic initiatives remain largely ineffective, it is argued that various local and international actors in the supply chains have a key role to play in actively enforcing this international standard to help support an economy free from the curse of child labour. This article proposes that an international legally binding agreement among global importers, unions, and local stakeholders to improve the child labour situation may provide the best mechanism to eliminate this problem from various supply chains in Bangladesh.